HUBUNGAN PENGETAHUAN DAN PENERAPAN KESEHATAN DAN KESELAMATAN KERJA DENGAN HASIL KERJA PRAKTEK BATU DAN BETON MAHASISWA PENDIDIKAN TEKNIK BANGUNAN JURUSAN TEKNIK SIPIL FT-UNP - Wahyudi Fauzi; Nurhasan Syah (Teknik Sipil Universitas Negeri Padang, 2021)
Abstract : This study aims to find out how much knowledge and application of K3 and the results of the Building Engineering Education Student Practicum Civil Engineering Department FT-UNP class 2019 and to find out the relationship between K3 knowledge and the results of student practicum at the Civil Engineering Construction Workshop FT-UNP. The population in this study were all students who took the stone and concrete practice course in the semester of January-June 2020 totaling 146 students and the research sample using proportional random sampling technique randomly with a total of 49 samples. The results of the study showed that (1) the knowledge and application of K3 of Building Engineering Education Students, Department of Civil Engineering, FT-UNP class of 2019 was in the medium category. The results of data analysis that has been carried out, obtained a percentage score of 78.84%. This shows that the 2019 Civil Engineering Department Building Engineering Students, FT-UNP, have moderate knowledge and application of K3. (2) The results of the 2019 Civil Engineering Department Building Engineering Education Student practicum are included in the high category. The results of data analysis that has been carried out, obtained a high score percentage of 80.07%. (3) there is a significant positive relationship between knowledge and the application of K3 with the results of the practicum of Building Engineering Education Students, Civil Engineering Department, Faculty of Engineering, University of Indonesia. This is indicated by the Pearson product moment correlation coefficient of 0.722 and is included in the strong category.